Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Symptoms in Pectus Deformities: A Scoring System for Subjective Physical Complaints - Ewert, Franziska; Syed, Julia; Kern, Sonja; Besendörfer, Manuel; Carbon, Roman T.; Schulz-Drost, Stefan (Thoracic and Cardiovascular Surgeon, 2017)
Background The literature is silent on the relationship between symptoms and the Haller index. Nor is there a classification of the severity of the physical complaints. Materials and Methods Retrospectively, data from 128 patients (102 funnel, 25 pigeon chest patients, and 1 mixed type) were evaluated. To objectify the symptoms, we developed a score to describe the level of physical ailments. This score includes 10 different symptoms as well as the situation or frequency in which they occur and an impact factor. This depends on how much they affect everyday life. Results Pectus excavatum patients express physical complaints more frequently than pectus carinatum patients who actually suffer more from psychological stress. We could not find a correlation between the Haller index and symptoms or levels of ailment. Conclusion Pectus deformities are likely to cause physical and psychological complaints. Since the subjective symptoms did not show any correlation to the chest severity index, they are supposed to be independent from the deformity's extent.
EVALuna2:35787